Physiological Changes and Interactions Between Microbiome and the Host During Pregnancy - Zakaria, Zain Zaki; Al-Rumaihi, Shouq; Al-Absi, Rana S.; Farah, Huda; Elamin, Muram; Nader, Rahaf; Bouabidi, Salma; Suleiman, Sara Elgaili; Nasr, Shahd; Al-Asmakh, Maha (Frontiers in Cellular and Infection Microbiology, 2022)
In recent years, it has become clear that microbiome play a variety of essential roles in human metabolism, immunity, and overall health and that the composition of these microbiome is influenced by our environment, diet, weight, hormones, and other factors. Indeed, numerous physiological and pathological conditions, including obesity and metabolic syndrome, are associated with changes in our microbiome, referred to as dysbiosis. As a result, it is not surprising that such changes occur during pregnancy, which includes substantial weight gain and significant changes in metabolism and immune defenses. The present review relates physiological changes during pregnancy to alterations in the microbial composition at various sites, including the gut, oral cavity, and vagina. Pregnancy has been linked to such microbial changes, and we believe that, in contrast to certain disease states, these microbial changes are vital for a healthy pregnancy, probably through their influence on the mother’s immunological, endocrinological, and metabolic status.